2015
DOI: 10.1039/c4gc02381a
|View full text |Cite
|
Sign up to set email alerts
|

Lignin repolymerisation in spruce autohydrolysis pretreatment increases cellulase deactivation

Abstract: An autohydrolysis pretreatment that suppresses lignin repolymerisation helps overcoming the recalcitrance of softwood for enzymatic hydrolysis of its cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 46 publications
8
133
2
1
Order By: Relevance
“…Such a mechanism is able to explain lignin solubilization in hot water conditions that cannot be attributed to acid catalyzed cleavage of β- O -4 linkages in lignin due to an autohydrolysis reaction [21, 22]. As in LHW flowthrough pretreatment at relatively short residence times, acetic acid liberated from acetylated xylans is removed from the reactor before it can cause a drop in solution pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism is able to explain lignin solubilization in hot water conditions that cannot be attributed to acid catalyzed cleavage of β- O -4 linkages in lignin due to an autohydrolysis reaction [21, 22]. As in LHW flowthrough pretreatment at relatively short residence times, acetic acid liberated from acetylated xylans is removed from the reactor before it can cause a drop in solution pH.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, flowthrough pretreatment removes these lignin-oligomer fragments before they have time to breakdown to lower solubility products [19]. Other than a lignin-hemicellulose fragmentation mechanism, some studies indicated that lignin depolymerization at acidic conditions can proceed through formation of carbenium intermediates followed by cleavage of β- O -4 linkages in lignin [2022]. As a result of enhanced lignin removal by flowthrough pretreatment, digestion of the glucan left in flowthrough solids by enzymes can achieve near theoretical glucan yields [23].…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that products resulting from the partial degradation of lignin and lignin fragments were removed by the neutral and acidic detergents with hemicelluloses. A slight increase in ADL content was observed after the fourth pretreatment cycle, indicating a gradually increasing degree of repolymerization of lignin (Pielhop et al 2015). The decrease in SHS content was consistent with the degradation of cellulose, and subsequent removal of degradation products by the acidic detergent.…”
Section: Changes In the Chemical Components Of Ebmentioning
confidence: 55%
“…Softwoods are characterized by being more recalcitrant to enzymatic hydrolysis than hardwoods or agricultural residues owing to their type and content of lignin . In addition, the major hemicelluloses in softwoods are galactoglucomannans (GGMs), whereas xylans are the dominant hemicelluloses in other lignocellulosic materials . Pinus radiata is a versatile, fast‐growing, medium‐density softwood, which can be employed for a wide range of end uses.…”
Section: Introductionmentioning
confidence: 99%